Non-Proteinogenic Amino Acids - Filip, Nina; Elena Iancu, Cristina (IntechOpen, 2018)
The first description of homocysteine (Hcy), a non-proteinogenic amino acid, was introduced in a case study more than 70 years ago. In recent years, numerous studies have shown a positive correlation between serum levels and various diseases, especially vascular pathology. Vitamins B6, B12, and folic acid play a major role in controlling homocysteine levels. In this book are presented both methods for the determination of homocysteine and its involvement in human pathology. Homocysteine levels can be taken as an early indicator for the detection of cardiovascular diseases because Hcy levels increase after a myocardial infarction or stroke.